The measure of a king : forging English Royal reputations 1066-1272 - Schmidt, Dagmar; Justus Liebig University Giessen (My University, 2014)
The good, the bad, the inept, the brave and the foolish English historiography is peppered with remarkable kings whose reputations cling to them despite the best efforts of historians. Yet what is it that makes a king? Even today, kingly demeanour reverberates with positive imagery; the ideal medieval king, a staple of fantasy and fairy tales, is a spectre easily conjured from collective memory. This very consciousness has ever been quick to judge its rulers: in cultural memory, medieval kings are handed down with an assessment of their respective kingliness. Upon which foundations do we base these opinions, these images of kings? Certainly not on historical research. Judging events and their agents is, indeed, in the best tradition of historical discourse. Current evaluation, especially with regard to the Middle Ages, may daintily array itself in an articulate attire of conjunctive, donning rather the apparel of assessing than judging but medieval appraisal of rulers and their deeds is not nearly as tentative in its conclusions. Yet it is these certainly not unbiased narrations of kings, and the adaptations that followed, that have significantly shaped collective perceptions of who can and who cannot be regarded as a good king. Contemporaries measured kings on the basis of a complex system of values, and it is crucial to know that it was not royal policy that determined historical judgement. Many writers were a long way from court and chancery. A good story, however, travelled and travelled far. For a king, both his successful kingship and his literary afterlife depended on how he fitted into the worldly and ecclesiastical ideals of his time, how he staged himself, how well he managed to clothe political decisions in the garb of the symbolically significant. Generations of historians have laboured to reconstruct a scaffold of historic fact upon which to base their evaluations. With this scaffold established, the book consciously turns its back on explanations, arguments and comparisons, and delves into that which too often has been scorned as fiction. It dissects the exaggerated, the unbelievable, the highly judgemental, perusing the tales of medieval storytellers for their implicit meaning. Side-by-side analysis of these stories suggests that each preposterous claim, each brandished sword, each display of emotion, each unseasonal bolt of lightning had its part in the forging of royal reputation. The book re-constructs a system of contemporary values and political thought, shaping it into a grid of five spheres of royal policy and contemporary judgement: a king s character and family, his court and retainers, his juridical acts, his behaviour in war and his conduct towards the Church. Each king is analysed individually, the entirety of his evaluation easily accessible through sub-chapters. This narrative analysis, based exclusively on contemporary source material, is the core of the book: the detailed image of each individual monarchlaid out for inspection, unwarped by later perception. With these images laid out, the book proceeds to sketch out what became of them. Kings were rarely allowed to rest in their tombs. Idealised, demonised, streamlined to fit a certain interpretation of their lives and deeds, they became epitomes of their respective style of kingship. Individual strands of narration were twined and refined until they formed images of individual kings that were to last, celebrating the good and condemning the bad.

Der ideale mittelalterliche König er reitet, herrscht, beschützt und kämpft noch immer, in einer kollektiv getragenen Vorstellungswelt, die weiß, was er zu leisten hat. Auch tatsächliche mittelalterliche Herrscher kämpfen in Interpretationen ihres Königtums weiter und das nicht selten gegen dieses Idealbild. Jedem ehemaligen König haftet ein gewisser Ruf an, der, teilweise entgegen aller Erkenntnisse der Geschichtswissenschaft, populär weiter besteht. Wie aber entsteht der gerechtigkeitsliebende Kämpfer der Vergangenheit, wie der despotische Tyrann? Es sind Geschichten, die ein Bild tradieren, formen, festigen; Geschichten, die sich in den seltensten Fällen um die alltäglichen Belange des Königtums ranken, sondern ihren Ursprung in Gesten, Symbolen, Ritualen nehmen, in Selbststilisierung und Fremddarstellung. Die Wurzeln ebensolcher Geschichten betrachtet das Projekt. Diese vergleichende Studie acht englischer mittelalterlicher Könige versucht aufzuklären, wie sich der Ruf eines Herrschers formt was es ist, dass einen guten von einem schlechten Herrscher trennt.
Das Maß eines Königs : das Entstehen englischer Königsreputationen 1066-1272
Keywords: England; Königtum; Symbolische Kommunikation; Mittelalter; Chronistik; England; Middle Ages; kingship; chronicle; symbolic communication; ddc:940